The Last Mycenaeans and Their Successors. An Archaeological Survey с. 1200 – с. 1000 B. C. - Desborough, V. R. d’A. (1964)
spez. Chapter VIII (pp. 196-214) The East Mediterranean: Cyprus, Asia Minor, Syria, the Philistines.